PENGUATAN HAK-HAK PEREMPUAN (SEBAGAI BAGIAN DARI HAK ASASI MANUSIA) DALAM KONSTITUSI - Yuli Asmara Triputra (JOURNAL EQUITABLE, 2017)
The main issue has always been inspiring the development of the principles of a constitutional state is the limitation of the power and protection of human rights. The presence of women in the life of the nation can not be denied. To that end, Indonesian women also need to study and understand their constitutional rights as citizens within the framework of state law. The question is, when talking about women's rights in the constitution, it will be confronted with several obstacles, including public acceptance of it is still very low. In connection with this, then it should be understood implementation of the values of human rights in the constitution. UUD 1945 as Constitution of Indonesia formulated that the protection of human rights is not aimed only at a particular group of people but to every citizen of Indonesia. This is seen from the formulation that uses the phrase "everyone", or "every citizen", which indicates that the constitutional rights possessed by every individual citizen without distinction, whether based on ethnicity , religion, political belief, or gender. Even the UUD 1945 also affirms that "everyone is entitled to be free from discriminatory treatment on any basis and the right to protection against such discriminatory treatment". Thus, if there are conditions or actions that discriminates against a particular country, it violates human rights and the constitutional rights of citizens, and by itself contrary to the constitution of Indonesia. Therefore, human rights are those rights which is constitutionally recognized, then the violation of human rights is a violation of the constitution. Thus, it can be concluded that every female Indonesian nationals have the same constitutional rights of Indonesian citizens were male. Strengthening women's rights contained in the constitution, it needs the support of all parties, particularly the women themselves by growing a culture of constitutional awareness, especially related to women's constitutional rights